2019
DOI: 10.1016/j.jsps.2019.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Gliclazide alone or in combination with atorvastatin ameliorated reproductive damage in streptozotocin-induced type 2 diabetic male rats

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…A case report of a 35-year-old man with primary infertility, a slight increase in glucose levels and overweight showed a deleterious effect of liraglutide on male reproductive function [ 110 ]. On the other hand, some authors [ 111 ] reported that gliclazide, alone or in combination with atorvastatin, ameliorated reproductive damage in streptozotocin-induced type 2 diabetic male rats.…”
Section: Treatment Of Mets and Its Impact On Semen Qualitymentioning
confidence: 99%
“…A case report of a 35-year-old man with primary infertility, a slight increase in glucose levels and overweight showed a deleterious effect of liraglutide on male reproductive function [ 110 ]. On the other hand, some authors [ 111 ] reported that gliclazide, alone or in combination with atorvastatin, ameliorated reproductive damage in streptozotocin-induced type 2 diabetic male rats.…”
Section: Treatment Of Mets and Its Impact On Semen Qualitymentioning
confidence: 99%
“…In recent years, several therapeutic interventions have been explored in rats to target different molecular pathways involved in diabetic-induced male testicular dysfunction. A marked structural and functional impairment of reproductive function in diabetic rats has been reported ( Mao et al, 2018 ; Barsiah et al, 2019 ; Öztaş et al, 2019 ). In the testis, a significant disruption of seminiferous tubular architecture with decreased spermatic content and atrophied germinal epithelium and interstitial tissue was noticed ( Mao et al, 2018 ; Barsiah et al, 2019 ; Öztaş et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…A marked structural and functional impairment of reproductive function in diabetic rats has been reported ( Mao et al, 2018 ; Barsiah et al, 2019 ; Öztaş et al, 2019 ). In the testis, a significant disruption of seminiferous tubular architecture with decreased spermatic content and atrophied germinal epithelium and interstitial tissue was noticed ( Mao et al, 2018 ; Barsiah et al, 2019 ; Öztaş et al, 2019 ). These changes are secondary to chronic metabolic complications of diabetes including chronic hyperglycemia, insulin resistance, and dyslipidemia which initiate an inflammatory response as demonstrated by positive testicular immune staining for TNFα and a significant increase in serum TNFα and IL6 ( Kwon and Pessin, 2013 ; Long et al, 2018 ; Barsiah et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Ma le reproduc t ive f unc t ion is compromised by diabetes mellitus, a major global health concern nowadays. [1,2] Hyperglycemia-induced massive generation of mitochondrial oxygen species of high reactivity (OSHR) can bring several difficulties in different organs, including testis. [3] Reports have demonstrated that chronic hyperglycemia results in alteration of androgenesis, damage of testicular tissue, and impairment of spermatogenesis that ultimately induces male subfertility.…”
Section: Introductionmentioning
confidence: 99%